Ethno-gynecological Cognizance of Phytomedicine Used by Tribes of Central and Eastern India: An Indigenous Heritage - Balkrishna, Acharya; Semwal, Ankita; Srivastava, Deepika; Sharma, Nidhi; Arya, Vedpriya (Faculty of Pharmacy, Universitas Gadjah Mada, 2025)
Ethnomedicinal information that exists with individuals from diverse regions is rapidly dwindling owing to a lack of interest among the young in imbibing traditional information from elderly home herbal healers, which is their golden heritage. There are huge benefits of indigenous prescriptions and using medicinal herbs for the treatment of many ailments. Tribal people are ignorant of evidence-based research on herbs, which can assist to improve their knowledge worldwide with scientific backing. This research is an attempt to document essential medicinal plants utilized by indigenous people of Central and Eastern India to treat gynecological disorders. The information was acquired from a literature search in electronic databases such as PubMed, Google-Scholar, SpringerLink, Scopus, and Wiley up to 2023. About 80 plants have been listed which have been reported to be used for the treatment of different gynecological disorders by the indigenous people of Central and Eastern India to treat gynecological disorders. Additionally, several scientific studies supporting the usage of the plant have been also described with their mechanistic insights. Since drug discovery from medicinal plants continues to provide a new array and important leads against various pharmacological targets, an effort to collect medicinal plants and their associated traditional knowledge could serve as an important tool for the discovery of new potent compounds. The extremely intriguing findings for gynecological illness necessitate further investigation, while the efficacy of numerous traditional phytomedicines must be assessed for their pharmacological confirmation before they can be embraced universally for the benefit of humanity.